Gestión en la autorización de cupos para el servicio de taxis que emite la Agencia de Transito Municipal del Canton Babahoyo - Calero Garcia, Alicia Margoth (2019)
TRANSVIAL-EP, works in alliance with other public companies including: The ATN, the Terrestrial Terminal and the ATM, within the ATM is the department of Enabling Titles in which from 2017 see the increase in quotas for the Taxi service provision, in the present case study the sub-line of Administrative Management Model submersion is immersed, the research methodology that adheres to this case study is the hypothetical-deductive method, because it is real problems and consequences of these, to reduce the problems identified will be issued the increase in quotas each period